Water Quality Monitoring and Classification at Panchor River - Enyau, Efrenno Melina; Johanis, Hilmi Yadi; Roslan, Akmal Ikhwan Fikri; Ahmad, Nor Farah Atiqah (Multidisciplinary Applied Research and Innovation, 2023)
Water pollution is one of the many types of pollution that exist in the post-revolutionary era. Rivers, as one of the water resources, are easily polluted, and water pollution is hazardous to the environment and human health. As a result, the study concentrated on monitoring the water quality and classification of the Panchor River in Johor, Malaysia. The goals of this study are to collect quantitative data on the physical, chemical, and biological characteristics of the river, as well as to determine the class of water in the river. This study was also carried out to raise awareness among Panchor residents about the importance of water quality. In addition to carrying out this project, four experiments to analyse the water sample were carried out: Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), and Ammoniacal Nitrogen. Furthermore, the Malaysian National Water Quality Standard was used as a reference to measure water quality and classify the water sample. Finally, it is critical to monitor the cleanliness of water sources in order to prevent water pollution. According to the results of the experiments, the Panchor River water quality index is in class III and is classified as slightly polluted.